2019
DOI: 10.1371/journal.pone.0221302
|View full text |Cite
|
Sign up to set email alerts
|

Darcy-Forchheimer nanofluidic flow manifested with Cattaneo-Christov theory of heat and mass flux over non-linearly stretching surface

Abstract: This research article aims to disclose the features of nanofluidic flow manifested with Cattaneo-Christov model of heat and mass flux over non-linearly stretching surface. An incompressible visco-elastic nanofluid saturates the given porous medium through Darcy-Forchheimer relation. A non-uniformly induced magnetic effect is considered to accentuate the electro-magnetic and thermal conductivity of the base fluid. The model is restricted to small magnetic Reynolds. Boundary layer assumptions are incorporated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 51 publications
0
46
0
Order By: Relevance
“…Rasool et al [29] reported a Darcy relation in nanofluids flow over nonlinearly stretching sheet/surface resulting some interesting variations in heat and mass transport. In another article, Rasool and Zhang [30] reported the characteristics of Darcy relation and MHD (Magnetohydrodynamics) together with Cattaneo-Christov theory of heat and mass flux over nonlinearly stretching surface. The results were obtained through homotopy approach.…”
Section: Introductionmentioning
confidence: 99%
“…Rasool et al [29] reported a Darcy relation in nanofluids flow over nonlinearly stretching sheet/surface resulting some interesting variations in heat and mass transport. In another article, Rasool and Zhang [30] reported the characteristics of Darcy relation and MHD (Magnetohydrodynamics) together with Cattaneo-Christov theory of heat and mass flux over nonlinearly stretching surface. The results were obtained through homotopy approach.…”
Section: Introductionmentioning
confidence: 99%
“…Shafiq et al 4 studied Casson Marangoni forced convection flow of nanofluid caused by temperature and concentration gradients over an infinite disk under the influence of inclined magnetic field. Rasool and Zhang 5 manifested Cattaneo–Christov model on heat and mass diffusion of nanofluid flow in non‐Darcian porous medium by a nonlinear stretching sheet. Rasool et al 6 interpreted the mechanism of forced convection flow of second grade nanofluid with Lorentz force and Maragoni effect.…”
Section: Introductionmentioning
confidence: 99%
“…A two‐phase fluid‐flow model is used by RamReddy et al considering mixed convection. Numerous related studies can be read in references and references cited therein.…”
Section: Introductionmentioning
confidence: 99%